2011
DOI: 10.1016/j.abb.2010.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Sulfenic acids as reactive intermediates in xenobiotic metabolism

Abstract: Sulfenic acid reactive intermediates are formed during the oxidation of cysteine residues of proteins and play key roles in enzyme catalysis, redox homeostasis and regulation of cell signalling. However few data are presently available on the formation and fate of sulfenic acids as reactive intermediates during the metabolism of xenobiotics. This article is a review of the xenobiotic metabolism situations in which the intermediate formation of a sulfenic acid has been reported. Formation of these intermediates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 53 publications
4
78
0
Order By: Relevance
“…21,6466 Formation of reactive, electrophilic intermediates by the oxidative metabolism of thiophenes can induce toxicity, as reported for suprofen and tienilic acid. 6570 On the other hand, thiophene-containing drugs like eprosartan and rivaroxaban are neither bioactivated nor toxic.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…21,6466 Formation of reactive, electrophilic intermediates by the oxidative metabolism of thiophenes can induce toxicity, as reported for suprofen and tienilic acid. 6570 On the other hand, thiophene-containing drugs like eprosartan and rivaroxaban are neither bioactivated nor toxic.…”
Section: Resultsmentioning
confidence: 89%
“…These pathways yield electrophilic, unstable thiophene S-oxides, 64 thiophene epoxides, 69 and sulfenic acids. 66 Notably, mass spectrometry experiments cannot reliably determine which bioactivation pathway leads to reactive metabolites because the thiophene S-oxide and the thiophene epoxide have the same mass and charge. This creates some ambiguity in the literature about the exact pathway by which some thiophenes are bioactivated.…”
Section: Figurementioning
confidence: 99%
“…This could indicate that other methimazole metabolites other than N -methylthiourea are responsible for ROS formation induced by this drug. In previous investigations, it has been shown that the N -methylthiourea produced during methimazole metabolism is further metabolized to reactive metabolites, which are capable of causing cytotoxicity [16, 17]. The protective effect of taurine against N -methylthiourea cytotoxicity in rat hepatocytes could be capable of inactivating these reactive metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…40 Sulfonic and sulfenic acids are reactive electrophilic species which are capable of interacting with several intracellular targets such as different proteins. 41,42 In the current study, we found that NMT administration significantly damaged liver mitochondria both in vitro and in vivo. NMT reactive metabolites might also be involved in the mitochondrial injury induced by this chemical in vivo (Figure 7).…”
Section: Discussionmentioning
confidence: 76%